Penerapan Metode Hungarian dalam Penugasan Dosen Pengampu Mata Kuliah Program Studi Matematika FMIPA Universitas Mataram - Muhammad Khairurradziqin; Ahmad Tedi Ruslan; Dzakiyatul Mardliyah; Fahmi Handika; Mamika Ujianita Romdhini (University of Mataram, 2020)
The tight schedule of lecture activities requires accuracy so that it always runs smoothly. Lecturer assignments play an important role to ensure the smooth lecture activities. Problems that often occur in the assignment of these lecturers need to be avoided. In an effort to reduce the risk of problems that occur in the assignment of lecturers, it is necessary to make a structured system with the right method. Hungarian method can be said very appropriate for this assignment problem because each course will only be charged to one lecturer. Another advantage of using the hungarian method in this lecturer assignment model is also because it uses the preferences of prospective lecturers as subjects of measurement. Each lecturer will take courses according to their best preferences with the expectation that the lecturer will have more mastery in the courses that he will teach.